1996
DOI: 10.1023/a:1016058123659
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Provided enthalpy and volume changes at the transitions are accurate enough, it is possible to draw a p, T diagram that accounts for the stability hierarchy of polymorphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 4 publications
3
13
0
Order By: Relevance
“…At temperature about 400 K, β-polymorph is transformed to γ-polymorph. While the α−to γtransition temperature obtained from 14 N NQR, is the same as the one obtained by the DSC measurement [38,42], the βto γtransition temperature obtained from 14 N NQR measurements is about 10 K higher. From Figures 3 and 6 it is additionally evident that α-polymorph is not abundantly directly transformed to γ-polymorph, but preferably via the formation of intermediate β-polymorph that then transforms into γ-polymorph.…”
Section: N Nqr In Sulfanilamidesupporting
confidence: 71%
“…At temperature about 400 K, β-polymorph is transformed to γ-polymorph. While the α−to γtransition temperature obtained from 14 N NQR, is the same as the one obtained by the DSC measurement [38,42], the βto γtransition temperature obtained from 14 N NQR measurements is about 10 K higher. From Figures 3 and 6 it is additionally evident that α-polymorph is not abundantly directly transformed to γ-polymorph, but preferably via the formation of intermediate β-polymorph that then transforms into γ-polymorph.…”
Section: N Nqr In Sulfanilamidesupporting
confidence: 71%
“…Sulfanilamide was found to crystallize in at least four different polymorphs: α, β, γ, and δ (see Figure S1, Supporting Information). The occurrence of polymorphism in SA has been ascribed to the relevance of several types of intermolecular interactions in determining the crystal structures of the compound, in particular intermolecular hydrogen bonds of the N–H···OS type and dispersion interactions between aromatic rings. These interactions allow for establishment of different types of cross-linked three-dimensional networks, in a similar way as found, for example, for pyrazinamide …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the andˇforms must be enantiotropically related, but the situation in respect of˛/ˇand˛/ is not clear. Burger 13 and Toscani and co-workers 24,25 reported the˛anď forms as monotropically related, but this is partly based on small melting enthalpy differences on samples of doubtful polymorphic purity. Sekiguchi et al 14 suggested that they are enantiotropes with a transition point below room temperature.…”
Section: Introductionmentioning
confidence: 99%